M. Umer Chapra's Islamic Economic Thought in the Context of Contemporary Era - Ririn Anjani Rangkuti (Journal of Nusantara Economy, 2024)
Islamic economic thought continues to play an important role in formulating solutions to global economic challenges. This article specifically explores the thinking of M. Umer Chapra, a prominent Islamic economic scholar, and analyzes its relevance in dealing with contemporary economic complexities. The discussion begins by providing a background on the importance of Islamic economic thought, followed by a research objective that details the actuality of M. Umer Chapra's thought in addressing current global economic problems. The article highlights the basic concepts of Islamic economics, especially the principles of wealth distribution and economic justice, focusing on Chapra's holistic approach. M. Umer Chapra's biography and his contributions to the development of Islamic economics are analyzed in depth to provide contextual understanding. Through comparison with other economic thought, both Western and traditional, the article explores the similarities and differences in economic views, providing a comprehensive picture of M. Umer Chapra's distinctive contributions. The implementation of Chapra's thoughts in economic practice is demonstrated through case studies, while challenges and opportunities in applying Islamic economic concepts are presented in detail.